THE DIRECTION OF SPACE REGULATION IN GLOBAL DYNAMICS - Agus Pramono (Fakultas Hukum, Universitas Diponegoro, 2017)
Space regulation initially acts as the orientation for activities in space which primarily concerns with research and development. As space exploration progresses, the regulation took a more practical direction which covers not only civil but also commercial activities. In line with this, development in commercial space activities took place such as telemetrics, remote sensor, space transportation, space industry, space tourism, space insurance, etc. To ensure that the commercialization of space activities is performed in a peaceful and safe manner as well as in ways that benefit all people, regulations in the form of anticipative laws are needed. These measures cover legal issues. Space commercialization is closely related to many aspects of life such as politics, social, economy, and security and defense which have been experiencing rapid development in that the presence of regulation for modern space law regime becomes an absolute necessity.